Improving Financial Management Behavior Influenced by Financial Knowledge, Financial Attitude, and Gender in Housewives - Yohana, Salsa Nur; Widiastuti, Anna (Jurnal Akuntansi & Keuangan Unja, 2026)
Housewives play a crucial role in family financial management. However, low financial literacy and attitudes toward finance, as well as gender differences in financial decision-making, remain challenges. This study aims to analyze the influence of financial knowledge, financial attitudes, and gender on financial management behavior using a quantitative approach. The population of this study was 160 housewives in Jepara Regency, selected using random sampling techniques. The research instrument was a questionnaire, and data analysis was conducted using SmartPLS 4. The results indicate that financial knowledge, financial attitude, and gender have a significant direct influence on financial management behavior. This study emphasizes the importance of improving financial literacy, developing positive financial attitudes, and fostering gender equality in financial decision-making to support wiser financial management behavior among housewives. The theoretical contribution of this study tests the hypothesis that individuals’ tendency to engage in financial management behavior is influenced by positive attitudes and subjective norms (the opinions of significant others) as explained in the Theory of Planned Behavior. Meanwhile, the practical contribution provides a basis for developing educational programs that not only improve financial knowledge but also build positive attitudes and strengthen social norms that support good financial behavior among housewives.